Determinan Nilai Perusahaan Manufaktur : Model Pengujian dengan Chow-Test dan Hausman-Test - Evelyn Wijaya; Yusnita Octafilia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The aim of company establishing is to increase company’s value in order to give prosperity for its stakeholders. And there are many internal and external factors can influence the company’s value. So, this study has aim to analyze determinant of manufacture companies’s value by using Chow-Test and Hausman-Test. This study has 109 manufacture companies with purposive sampling method and uses panel data regression as data analysis method. The examination of study model by using Chow-Test and Hausman-Test shows that the proper study model examination is Fixed Effect Model (FEM). The result of Fixed Effect Model shows that company size influences positifically and significantly on company’s value. Then, institutional ownership and investment policy influence negatively and significantly on company’s value. While, profitability, funding decision, devident policy, managerial ownership and cash holding do not influence significantly on company’s value. As there is supervision from institution party on management performance, it is going to make management do financial decision that related with company’s value movement carefully. Keywords: Company’s internal factors, Agency Theory and Company’s value